It is tuberculosis or melioidosis? a clinical diagnostic dilemma - Jamani, Nurjasmine Aida; Mohd Nor, Farah Hanani; Yatim, Yusnita (Malaysian Medical Association, 2021)
Pulmonary Tuberculosis (PTB) is an endemic disease in Malaysia and continues to cause great morbidity and mortality. However, the diagnosis and treatment may pose a challenge to the attending physician since other diseases such as melioidosis can mimic tuberculosis. Hence, the final diagnosis should be done thorough history of illness, physical examination, investigations, and interpretation of findings. We present here a case of a 27-year-old man who presented at our primary care clinic with underlying diabetes mellitus whose symptoms were suggestive of PTB, and who was treated with anti-tuberculosis but later his sputum grew culture Burkholderia pseudomallei